2015
DOI: 10.3389/fimmu.2015.00061
|View full text |Cite
|
Sign up to set email alerts
|

The Environment of Regulatory T Cell Biology: Cytokines, Metabolites, and the Microbiome

Abstract: Regulatory T cells (Tregs) are suppressive T cells that have an essential role in maintaining the balance between immune activation and tolerance. Their development, either in the thymus, periphery, or experimentally in vitro, and stability and function all depend on the right mix of environmental stimuli. This review focuses on the effects of cytokines, metabolites, and the microbiome on both human and mouse Treg biology. The role of cytokines secreted by innate and adaptive immune cells in directing Treg dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 231 publications
(212 reference statements)
2
93
0
3
Order By: Relevance
“…Similar results were also observed in other studies, where there is a decrease of suppressive ability of Tregs in SLE patients in modulating other Th cell subsets (13,17). The composition of the local milieu, including the types of cytokines, can influence Treg function (18). Some pro-inflammatory cytokines, such as IFN type I (IFN-α) and IL-6 have been found to affect Treg function in SLE patients (19,20).…”
Section: Development Of Th Cell Subset Percentages After Pristane Injsupporting
confidence: 73%
“…Similar results were also observed in other studies, where there is a decrease of suppressive ability of Tregs in SLE patients in modulating other Th cell subsets (13,17). The composition of the local milieu, including the types of cytokines, can influence Treg function (18). Some pro-inflammatory cytokines, such as IFN type I (IFN-α) and IL-6 have been found to affect Treg function in SLE patients (19,20).…”
Section: Development Of Th Cell Subset Percentages After Pristane Injsupporting
confidence: 73%
“…Recent studies, utilizing metabolome analysis and other investigative techniques, have revealed that the number of colonic Tregs in steady-state conditions are heavily influenced or even determined by the luminal concentration of propionate, butyrate, and perhaps acetate, produced by commensal bacteria [105][106][107]. The precise mechanisms by which SCFAs promote the production of colonic Tregs are still a matter of debate and may well vary with the SCFAs involved.…”
Section: Effects On Regulatory T Cell Productionmentioning
confidence: 97%
“…Moreover, recent studies highlighted the immunosuppressive potential of other cell types including uterine natural killer (uNK) cells and mesenchymal stem cells (MSCs) [8,9]. One of the hallmarks of regulatory cell populations is their remarkable plasticity as they can be positively or negatively modulated by a broad spectrum of cytokines, chemokines, growth factors and costimulatory signals that tailor their differentiation, expansion, stability and survival [10]. Moreover, although underappreciated for many years, emerging observations suggest essential roles for endogenous glycan-binding proteins or lectins and their corresponding glycosylated ligands in controlling the fate and function of immune regulatory cells [11].…”
Section: Immune Cell Homeostatic Programs Regulated By Galectin-glycamentioning
confidence: 99%